A Continuous Battle for Host-Derived Glycans Between a Mucus Specialist and a Glycan Generalist in vitro and in vivo - Kostopoulos, Ioannis; Aalvink, Steven; Kovatcheva-Datchary, Petia; Nijsse, Bart; Bäckhed, Fredrik; Knol, Jan; de Vos, Willem M.; Belzer, Clara (Frontiers in Microbiology, 2021)
The human gastrointestinal tract is colonized with a diverse microbial community, that plays a crucial role in human health. In the gut, a protective mucus layer, which consists of glycan structures, separates the bacteria from the host epithelial cells. These host-derived glycans are utilized by bacteria that have adapted to this specific compound in the gastrointestinal tract. In our study, we investigated the close interaction between two distinct gut microbiota members known to use mucus glycans, the generalist Bacteroides thetaiotaomicron and the specialist Akkermansia muciniphila in vitro and in vivo. The in vitro study, where mucin was the only nutrient source, indicated that B. thetaiotaomicron significantly upregulated genes coding for Glycoside Hydrolases (GHs) and mucin degradation activity when cultured in the presence of A. muciniphila. Furthermore, B. thetaiotaomicron significantly upregulated the expression of a gene encoding for membrane attack complex/perforin (MACPF) domain in co-culture. The transcriptome analysis also indicated that A. muciniphila was less affected by the environmental changes and was able to sustain its abundance in the presence of B. thetaiotaomicron while increasing the expression of LPS core biosynthesis activity encoding genes (O-antigen ligase, Lipid A and Glycosyl transferases) as well as ABC transporters. Using germ free mice colonized with B. thetaiotaomicron and/or A. muciniphila, we observed a more general glycan degrading profile in B. thetaiotaomicron while the expression profile of A. muciniphila was not significantly impacted when colonizing together, indicating that two different nutritional niches were established in mice gut. Thus, our results indicate that a mucin degrading generalist adapt to its changing environment, depending on available carbohydrates while a mucin degrading specialist adapts by coping with competing microorganism through upregulation of defense related genes.